Seroprevalens av antikroppar mot Encephalitozoon cuniculi hos friska tamkaniner - Eriksson, Anneli (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2007)
The aim of this study was to determine the prevalence of antibodies against the intracellular protozoan Encephalitozoon cuniculi in healthy pet rabbits. Encephalitozoonosis is an important differential diagnosis to ascending infection with Pasteurella multocida in the ears since a common symptom is vestibular syndrome. Samples were collected from healthy rabbits that were brought to an animal clinic in Stockholm for some kind of prophylactic procedure. The samples were analysed by an India-ink Immunoreaction test / Carbon Immunoassay. Of 106 rabbits 7 (6.6%) were seropositve. This can be compared to studies in other countries where they have found seroprevalences of 23-93%. No obvious predisposing factor such as breed, age, gender or background was identified. Comparison of the studied population to a randomly chosen population of rabbits with symptoms of encephalitozoonosis showed that the studied population had a markedly lower average age and a larger proportion of males.